2015
DOI: 10.18632/oncotarget.5060
|View full text |Cite
|
Sign up to set email alerts
|

Double autophagy modulators reduce 2-deoxyglucose uptake in sarcoma patients

Abstract: RationaleAccording to the metabolic symbiosis model, cancer stromal fibroblasts could be hijacked by surrounding cancer cells into a state of autophagy with aerobic glycolysis to help provide recycled nutrients. The purpose of this study was to investigate whether combined treatment with the autophagy inhibitor: hydroxychloroquine (HCQ) and the autophagy inducer: sirolimus (rapamycin, Rapa) would reduce glucose utilization in sarcoma patients.MethodsTen sarcoma patients who failed first-line treatment were enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Furthermore, Zhang et al found that 18 F-FDG accumulated predominantly in noncancerous stroma in a tumor model under fed status 26 . Moreover, Chi's group found that double autophagy modulator (rapamycin + hydroxychloroquine) treatment only reduced the SUVmax without affecting tumor growth 46 . As CAFs are the major component of the tumor stroma, these findings suggest that non-proliferative glycolytic CAFs increase the local accumulation of 18 F-FDG in tumors, and the SUVmax may be a perfect marker for anti-CAF therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Zhang et al found that 18 F-FDG accumulated predominantly in noncancerous stroma in a tumor model under fed status 26 . Moreover, Chi's group found that double autophagy modulator (rapamycin + hydroxychloroquine) treatment only reduced the SUVmax without affecting tumor growth 46 . As CAFs are the major component of the tumor stroma, these findings suggest that non-proliferative glycolytic CAFs increase the local accumulation of 18 F-FDG in tumors, and the SUVmax may be a perfect marker for anti-CAF therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple clinical trials have evaluated the effectiveness of autophagy inhibition in solid malignancies. [30][31][32][33][34][35][36][37][38] This is the first report, to our knowledge, of autophagy inhibition in lung disease. Our findings could have important application to other lung diseases such as COPD and idiopathic pulmonary fibrosis in which autophagy has been shown to be altered, and modulating autophagy could have therapeutic benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Whether rapamycin or rapamycin analogs have potential for improving healthspan and lifespan in humans is unclear, and their potential side effects are of significant concern. Rapamycin analogs that selectively target TORC1, which should have less side effects, have been proposed for treatment of diseases of aging (Arriola Apelo & Lamming, 2016;Bjedov et al, 2010;Chi et al, 2015;El-Chemaly et al, 2017;Miller et al, 2010).…”
Section: Proteostasismentioning
confidence: 99%